Hubungan Pencahayaan dan Shift Kerja dengan Kelelahan Mata Pada Pekerja di Laboratorium PMI Kota Surakarta Tahun 2025 - Kurniawan; Nur Ani; Wartini; Farid Setyo Nugroho (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
ABSTRACT Eye fatigue is a common occupational health issue experienced by workers, particularly due to inadequate lighting and rotating shift systems that disrupt the body’s biological rhythm. The TFOS report in 2023 stated that the global prevalence of digital eye fatigue reached 70.7%, highlighting the substantial role of workplace lighting and work schedules in contributing to visual discomfort. A preliminary survey at the laboratory of the Indonesian Red Cross (PMI) Surakarta revealed that nighttime lighting intensity was only 139 lux, with approximately 70% of night shift workers reporting symptoms of eye fatigue. This study aimed to determine the relationship between lighting and work shifts and the occurrence of eye fatigue among laboratory workers at PMI Surakarta. A quantitative cross-sectional design was employed, involving the total population of 39 laboratory workers selected through total sampling. Data were collected using the Visual Fatigue Index (VFI) questionnaire to assess eye fatigue and a lux meter to measure lighting intensity. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test. Results showed that most respondents (69.2%) worked in environments with lighting below the standard, 46.2% worked during day shifts, and 56.4% experienced eye fatigue. Statistical tests revealed a significant relationship between lighting and eye fatigue (p = 0.001), while no significant relationship was found between work shifts and eye fatigue (p = 0.065). Based on these findings, it was concluded that lighting plays a significant role in the incidence of eye fatigue, whereas work shifts do not show a statistically meaningful relationship. The study recommends that PMI Surakarta evaluate its workplace lighting systems and consider revising shift schedules to support visual health and worker productivity. Keywords: eye fatigue, lighting, work shift, laboratory